Characteristics and predictability of a supercell during HyMeX SOP1. (25th August 2016) - Miglietta, Mario Marcello; Manzato, Agostino; Rotunno, Richard
Abstract : An analysis is presented here of intense convection affecting the Friuli Venezia Giulia region (FVG, northeastern Italy) during the Intensive Observation Period 2b (IOP2b) in the first Special Observation Period (SOP1) of HyMeX (HYdrological cycle in Mediterranean EXperiment). The present study focuses on the first of three severe‐convection episodes that affected FVG on the morning of 12 September 2012. In the first episode, a supercell, which produced hail and severe damage to trees and buildings, was observed on the plain of FVG. The available observations are analysed together with a high‐resolution mesoscale model, in order to identify the relevant mechanisms for the formation and development of the cell. Six different simulations were performed starting at three different initial times, using respectively two different analysis/forecasts as initial/boundary conditions. A large spread in forecast precipitation is found among the six simulations. Only a few of the simulations were able to reproduce intense rainfall on the plain of FVG during the morning, although with significant differences in the rainfall distribution among them. One of the six simulations well reproduces the observed elongated distribution of the intense rainfall maximum; the characteristics of the cell responsible for this distribution are consistent with those expected for a supercell and its simulated evolution near the Adriatic coast agrees well with the other observations. Some instability parameters over the FVG plain and offshore (over the northern Adriatic Sea) are analysed every 5 min, showing that during this event the potential instability varies significantly over small space and time intervals and among the simulations. The best simulations have the best match to the observed potential instability calculated using the mean characteristics of the lowest 500 m layer.